Bacteriophages of Mycobacterium tuberculosis, their diversity, and potential therapeutic uses: a review - Fatemeh Zeynali kelishomi; Susan Khanjani; Fatemeh Fardsanei; Hediyeh Saghi Sarabi; Farhad Nikkhahi; Behzad Dehghani (BMC Infectious Diseases, 2022)
Abstract Tuberculosis (TB) caused by Mycobacterium tuberculosis (M. tuberculosis) is a highly infectious disease and worldwide health problem. Based on the WHO TB report, 9 million active TB cases are emerging, leading to 2 million deaths each year. The recent emergence of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) strains emphasizes the necessity to improve novel therapeutic plans. Among the various developing antibacterial approaches, phage therapy is thought to be a precise hopeful resolution. Mycobacteriophages are viruses that infect bacteria such as Mycobacterium spp., containing the M. tuberculosis complex. Phages and phage-derived proteins can act as promising antimicrobial agents. Also, phage cocktails can broaden the spectrum of lysis activity against bacteria. Recent researches have also shown the effective combination of antibiotics and phages to defeat the infective bacteria. There are limitations and concerns about phage therapy. For example, human immune response to phage therapy, transferring antibiotic resistance genes, emerging resistance to phages, and safety issues. So, in the present study, we introduced mycobacteriophages, their use as therapeutic agents, and their advantages and limitations as therapeutic applications.